STUDI ANALISIS PENINGKATAN FASILITAS PELAYANAN JALAN RUMAH SAKIT KOTA TASIKMALAYA - Ega Sri Wulandari; Dicky Nurmayadi; Farhan Sholahudin (Universitas Perjuangan Tasikmalaya, 2021)
Abstract— Tasikmalaya City Hospital Street is an urban road with road type 2/2 UD. The Hospital Street area is a place for public transportation to stop passengers, there are public hospitals, schools and shops that are busy with pedestrians. Hospital road infrastructure has several shortcomings, namely fading road markings, lack of traffic signs, road body parking which results in a decrease in vehicle speed, and more optimized safety of vehicle users and pedestrians. Analysis of road performance using the Indonesian Road Capacity Manual method (MKJI, 1997) and pedestrian characteristics using the Highway Capacity Manual method (HCM, 2000). Hospital roads have a traffic volume of 1108 pcu / hour with a road capacity of 2859.0288 pcu / hour, so the degree of saturation is 0.38 and results in a road service level at the